Deploying a real-time operating system on a reconfigurable internet of things End-device - Ribeiro, Ângelo (2019)
The Internet of Things (IoT) is enabling the connection of an infinity of physical objects to the Internet through the wide deployment of low-end embedded devices at the network edge. However, providing communication capabilities to such devices, which allows them to connect to the Internet seamlessly, is not straightforward. Such features require the adoption of a lightweight and standard network stack, commonly integrated with an embedded operating system (OS), mitigating the complexity of developing resource-constrained wireless nodes. To assist in such tasks, some existing motes explore reconfigurable technology to accelerate compute-intense tasks (application- or network-related) in dedicated hardware accelerators. This article describes the deployment of a real-time OS, RIOT, on a reconfigurable end-device architecture for IoT, the CUTE Mote. The CUTE mote is based on a heterogeneous solution that combines a hard-core microcontroller unit beside reconfigurable technology and an IEEE 802.15.4-compliant radio transceiver.